2021
DOI: 10.3390/ijms221910610
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Reduces Plin5 m6A Methylation through FTO to Regulate Lipolysis in Piglets

Abstract: Perilipin5 (Plin5) is a scaffold protein that plays an important role in lipid droplets (LD) formation, but the regulatory effect of leptin on it is unclear. Our study aimed to explore the underlying mechanisms by which leptin reduces the N6-methyladenosine (m6A) methylation of Plin5 through fat mass and obesity associated genes (FTO) and regulates the lipolysis. To this end, 24 Landrace male piglets (7.73 ± 0.38 kg) were randomly sorted into two groups, either a control group (Control, n = 12) or a 1 mg/kg le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In line with this hypothesis, the JAK inhibitor Ruxolitinib and the STAT3 phosphorylation inhibitor STATTIC both inhibited PLIN5 upregulation. This finding confirms previous reports showing PLIN5 being regulated by the JAK/STAT3 pathway after leptin treatment in adipocytes [ 46 , 47 ]. Therefore, we concluded that the JAK/STAT3 signaling axis mediates PLIN5 expression upon IL-6 stimulation in Hep3B.…”
Section: Discussionsupporting
confidence: 93%
“…In line with this hypothesis, the JAK inhibitor Ruxolitinib and the STAT3 phosphorylation inhibitor STATTIC both inhibited PLIN5 upregulation. This finding confirms previous reports showing PLIN5 being regulated by the JAK/STAT3 pathway after leptin treatment in adipocytes [ 46 , 47 ]. Therefore, we concluded that the JAK/STAT3 signaling axis mediates PLIN5 expression upon IL-6 stimulation in Hep3B.…”
Section: Discussionsupporting
confidence: 93%
“…These results highlighted the effect of specific DHA‐diet in mitochondrial biogenesis and skeletal muscle fiber via Fto /m 6 A, protecting against obesity‐induced decline in skeletal muscle function (W. Chen et al, 2022). Similarly, Wei et al (2021) treated male piglets with 1 mg/kg of leptin recombinant protein. After 4 weeks treatment, the authors found an upregulation of FTO , which in turn leads to the decrease of m 6 A methylation of mRNA Plin5 .…”
Section: Mitochondrial Rna Modifications and Its Enzyme Modifiers And...mentioning
confidence: 99%
“…An additional in vitro porcine found that overexpression of FTO decreased mRNA m 6 A methylation and increased the expression of Plin5 protein in adipocytes. The overexpression in vitro of Plin5 significantly reduces the size of lipid droplets, promotes the metabolism of triglycerides, and the operation of the mitochondrial respiratory chain, and increases thermogenesis, indicating that Plin5 m 6 A methylation through FTO affects lipid metabolism and energy consumption, providing a new preventive mechanism against obesity (D. Wei et al, 2021). Therefore, these studies can conclude that FTO is responsible for mt‐mRNA modifications that regulate mitochondrial biogenesis in adipose tissue and specifically, lipid metabolism and energy expenditure in obesity.…”
Section: Mitochondrial Rna Modifications and Its Enzyme Modifiers And...mentioning
confidence: 99%
“…In caponized chickens with low cellular lipid content, RXRG mRNA levels were significantly downregulated [39]. PLIN5 (Perilipin 5), a scaffolding protein, plays an important role in the formation of lipid droplets [40]. IMF is stored in lipid droplets, and overexpression of PLIN5 in vitro could significantly reduce the size of lipid droplets, promote the metabolism of triglycerides and the mitochondrial respiratory chain, and enhance thermogenesis.…”
Section: Discussionmentioning
confidence: 99%